2018
DOI: 10.3389/fonc.2018.00582
|View full text |Cite
|
Sign up to set email alerts
|

Technical Advances in Single-Cell RNA Sequencing and Applications in Normal and Malignant Hematopoiesis

Abstract: Single-cell RNA sequencing (scRNA-seq) has been tremendously developed in the past decade owing to overcoming challenges associated with isolation of massive quantities of single cells. Previously, cell heterogeneity and low quantities of available biological material posed significant difficulties to scRNA-seq. Cell-to-cell variation and heterogeneity are fundamental and intrinsic characteristics of normal and malignant hematopoietic cells; this heterogeneity has often been ignored in omics studies. The appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 106 publications
1
20
0
Order By: Relevance
“…TPO-DBs are able to deliver customized intensities of downstream TPO-R signals, and thus mimic the physiological conditions of the TPO regulation while more tightly controlling downstream signaling output. In addition, the TPO DBs split the functions of TPO with regard to megakaryopoiesis and HSC expansion, a unique feature, retained at least short-term stem-cell-like properties; thus, these culture conditions appear optimal for stem-cell maintenance.Using single-cell transcriptomics (scRNA-seq) in conjunction with protein expression studies, we confirmed that the stem cells generated by DBs (which we found partially block the activity of MPL) produce an original pool of stem cells in vitro(38,39). By clustering HSC and MPP we can conclude that after nearly two weeks of culture, the HSCAK111 populations are closer to HSC than MPP populations.…”
supporting
confidence: 58%
“…TPO-DBs are able to deliver customized intensities of downstream TPO-R signals, and thus mimic the physiological conditions of the TPO regulation while more tightly controlling downstream signaling output. In addition, the TPO DBs split the functions of TPO with regard to megakaryopoiesis and HSC expansion, a unique feature, retained at least short-term stem-cell-like properties; thus, these culture conditions appear optimal for stem-cell maintenance.Using single-cell transcriptomics (scRNA-seq) in conjunction with protein expression studies, we confirmed that the stem cells generated by DBs (which we found partially block the activity of MPL) produce an original pool of stem cells in vitro(38,39). By clustering HSC and MPP we can conclude that after nearly two weeks of culture, the HSCAK111 populations are closer to HSC than MPP populations.…”
supporting
confidence: 58%
“…Using single-cell transcriptomics (scRNA-seq) in conjunction with protein expression studies, we confirmed that the stem cells generated by DBs produce an original pool of stem cells in vitro ( 45 , 46 ). By clustering HSPCs and MPPs we can conclude that after nearly 2 wk of culture, the HSC AK111 populations are closer to HSPC than MPP populations.…”
Section: Discussionmentioning
confidence: 68%
“…In the present work, we revealed the changes of GER cells profiles by single-cell RNA sequencing technology (Baslan et al, 2012;Shapiro et al, 2013;Huang et al, 2018). We also observed the change of the expression and regulation of key genes and signaling pathways enriched biological processes in these clusters during cochlear development.…”
Section: Introductionmentioning
confidence: 64%